Natural Occurrence of Mycotoxin-Producing Fusaria in Market-Bought Peruvian Cereals: A Food Safety Threat for Andean Populations - Ducos, Christine (2021)
This research was funded by the French National Alliance for Life Sciences and Health, grant number ENV201408. S.B. has received funding from the European Union's Horizon 2020 Framework program under the Marie Sklodowska-Curie Actions, agreement number 823935. P.V.O. was supported by a postdoctoral fellowship from the French National Research Institute for Sustainable Development (IRD) (04077858). JPC was a recipient of a doctoral fellowship from the Peruvian National Council for Science and Technology (212-2015-FONDECYT).